Endobronchial Mimics of Primary Endobronchial Carcinoma: A Clinical Study of 25 Cases - Cynthia M Magro (Canadian Respiratory Journal, 2005)
While endobronchial lesions that present with symptoms of obstruction may be reflective of primary bronchogenic malignancy, there have been a number of reports of bronchial lesions other than primary bronchogenic carcinoma simulating primary endobronchial epithelial malignancy clinically. Twenty-five cases of symptomatic endobronchial disease were encountered with pathological assessment demonstrating an endobronchial process other than carcinoma, representing metastatic disease (breast, colon, renal, head and neck origin), fungal infection, Hodgkin's lymphoma, primary bronchogenic melanoma, lipoma, broncholith and inflammatory pseudopolyp. The present report underscores the potential pathogenetic heterogeneity encountered in lesions presenting with signs and symptoms of endobronchial obstruction, emphasizing the critical role of biopsy for establishing a definitive diagnosis.